Co(II), Ni(II), Cu(II), and Zn(II)-(E)-N’-(2-Hydroxybenzylidene)benzohydrazide Complexes: Design, Characterization, ADME Study, and Evaluation of Antibacterial Activity - Alam, Yusuf Syahril; Fitria, Nuraini; Adama, Amelia Bella Putri; Salsabilla, Shava Alifia; Duhita, Shinta Ratna; Santoso, Mardi; Martak, Fahimah (Indonesian Journal of Chemistry, 2026)
Four new hydrazone complexes were successfully synthesized from Co(II), Ni(II), Cu(II), and Zn(II) metal ions with the ligand (E)-N’-(2-hydroxybenzylidene)benzohydrazide. Structural elucidation was performed using CHNSO elemental analysis, FTIR, UV-vis, thermal analysis, and powder XRD. The FTIR spectra indicated the presence of coordination bonds in the form of M–N and M–O. The UV-vis spectrophotometer showed LMCT transitions. TGA characterization revealed that the Co(II), Ni(II), and Cu(II) complex compounds have an M:L ratio of 1:1, whereas the Zn(II) complex compound has an M:L ratio of 1:2. These findings were corroborated by the refinement results of the experimental and standard XRD diffractogram. Accordingly, the formulas of the Co(II), Ni(II), Cu(II), and Zn(II) hydrazone complexes are [Co(L)(Cl)(H2O)], [Ni(L)(H2O)2]Cl2, [Cu(L)(H2O)]Cl, and [Zn(L)2], respectively. Furthermore, based on the determined M:L ratios, the Co(II), Ni(II), and Cu(II) complexes are inferred to possess square planar geometries, while the Zn(II) complex is suggested to be octahedral. The ADME study, aimed at assessing their potential as drug candidates, revealed various pharmacological characteristics of the compounds. Antibacterial evaluation against Staphylococcus aureus (G+) and Escherichia coli (G−) showed the Cu(II) complex with the highest activity.